Prepaid electricity model in Zimbabwe: a cost-benefit analysis - Mujaji, Shingirai (Research of GSB, 2018)
To manage credit risk and improve working capital, many power utility companies have moved consumers from conventional post-payment for electricity to prepayment. Despite the growing use of this prepayment system, the welfare implications of this strategy are unclear and contested. The Zimbabwean utility company, Zimbabwe Electricity Transmission and Distribution Company (ZETDC), introduced prepaid meters in August 2012 and installed over 550,000 prepaid meters by the 31st of December 2015. This thesis' objective was to quantitatively assess the societal costs and benefits of introducing prepaid electricity to Zimbabwe, by calculating the net present value of the estimated annual costs and benefits over time. A qualitative analysis was also conducted, based on a consumer survey of 100 consumers who had switched from the post-paid to the prepaid system. The survey captured consumers' perceptions of the prepaid system's costs and benefits. Results of the study showed that both consumers and the utility company have benefited from the prepaid system. The average net benefit per user under the prepaid system was estimated at US$58.93 per annum. 74% of consumers surveyed confirmed having benefited from the switch to the prepaid system. The main policy recommendation, based on the results of the study, is for ZETDC to continue with its roll out of the prepaid system. However, as the research was limited to the current ZETDC prepaid consumer base of only domestic and small business users, a recommendation for future research would be to evaluate the costs and benefits for larger industrial consumers as well.